2005
DOI: 10.1158/1055-9965.epi-05-0105
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of GlutathioneS-Transferases and the Risk of Adult Brain Tumors: A Meta-analysis

Abstract: Background: Studies investigating the association between genetic polymorphisms of glutathione S-transferases (GST) and risk of adult brain tumors have reported conflicting results. The rationale of this meta-analysis was to determine whether GST variants increase the susceptibility of adult brain tumors by pooling data. Methods: Two investigators independently searched the HuGENet database, MEDLINE, EMBASE, conference articles, and manually reviewed bibliographies of retrieved articles. Papers were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 32 publications
4
46
2
1
Order By: Relevance
“…In that meta-analysis, the authors searched publications up to January 2005, and found no significant association between GSTM1 and GSTT1 polymorphisms and risk of glioma. In contrast, some of our findings were in disagreement with the results reported by Lai et al who found that the GSTT1 null genotype was significantly associated with an increased risk of meningioma (OR =1.95; 95% CI, 1.02-3.76, P = 0.046) (Lai et al, 2005). The main reason for this discrepancy may be that the statistical power is not sufficient to provide accurate effect of GSTT1 polymorphism on the risk of meningioma.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In that meta-analysis, the authors searched publications up to January 2005, and found no significant association between GSTM1 and GSTT1 polymorphisms and risk of glioma. In contrast, some of our findings were in disagreement with the results reported by Lai et al who found that the GSTT1 null genotype was significantly associated with an increased risk of meningioma (OR =1.95; 95% CI, 1.02-3.76, P = 0.046) (Lai et al, 2005). The main reason for this discrepancy may be that the statistical power is not sufficient to provide accurate effect of GSTT1 polymorphism on the risk of meningioma.…”
Section: Discussioncontrasting
confidence: 99%
“…Taken together, we may conclude that GSTM1 and GSTT1 homozygous deletion polymorphisms may not relate to the development of brain tumors. Some of our findings were similar to the results of a meta-analysis presented by Lai et al in 2005(Lai et al, 2005. In that meta-analysis, the authors searched publications up to January 2005, and found no significant association between GSTM1 and GSTT1 polymorphisms and risk of glioma.…”
Section: Discussionsupporting
confidence: 90%
“…A meta-analysis of eight studies with 1,630 gliomas, 245 meningiomas, and 7,151 controls found no association between glutathione S-transferases (GST) variants and adult brain tumors. 84 Neural carcinogens, such as dietary N-nitroso compounds (NOCs) from consumption of cured meats, were studied for the risk of gliomas. A pooled analysis of nine population-based studies failed to establish NOCs as a causal agent for glioma.…”
Section: Pbts Molecular Epidemiologic Studies With Focus On Metabolismmentioning
confidence: 99%
“…In contrast, Lai et al (2005) conducted a meta-analysis of the association between genetic polymorphisms of GSTs and the risk of adult brain tumors (Lai et al, 2005), and their results did not suggest any relationship between those two. Additionally, several large-sample, case-control studies that have been conducted by various authors around the world have reported conflicting results after previous meta-analysis.…”
Section: An Updated Pooled Analysis Of Glutathione S-transferase Genomentioning
confidence: 98%
“…Because GSTs are important in the cellular detoxification of carcinogens, genetic variants of GSTs have been studied extensively in relation to cancer risk. A search of the literature prior to June 2011 revealed thousands of studies regarding the relationship between GST genotypes and breast (Bailey et al, 1998), lung (Zheng et al, 2006, colon (Zhong et al, 1993), brain (Lai et al, 2005), bladder (Hung et al, 2004), prostate (Ntais et al, 2005) and other types of cancer (Gao et al, 2011). These studies have primarily focused on single nucleotide polymorphisms (SNPs) in GSTM1, GSTT1, and GSTP1.…”
Section: An Updated Pooled Analysis Of Glutathione S-transferase Genomentioning
confidence: 99%